Hierarchies in the Decentralized Welfare State: Prioritization in the Housing Choice Voucher Program. Issue 1 (February 2023) - Zhang, Simone; Johnson, Rebecca A.
Social provision in the United States is highly decentralized. Significant federal and state funding flows to local organizational actors, who are granted discretion over how to allocate resources to people in need. In welfare states where many programs are underfunded and decoupled from local need, how does decentralization shape who gets what? This article identifies forces that shape how local actors classify help-seekers when they ration scarce resources, focusing on the case of prioritization in the Housing Choice Voucher Program. We use network methods to represent and analyze 1, 398 local prioritization policies. Our results reveal two patterns that challenge expectations from past literature. First, we observe classificatory restraint, or many organizations choosing not to draw fine distinctions between applicants to prioritize. Second, when organizations do institute priority categories, policies often advantage applicants who are formally institutionally connected to the local community. Interviews with officials, in turn, reveal how prioritization schemes reflect housing agencies' position within a matrix of intra-organizational, inter-organizational, and vertical forces that structure the meaning and cost of classifying help-seekers. These findings illustrate how local organizations' use of classification to solve on-the-ground organizational problems and manage scarce resources can generate additional forms of exclusion.